A Novel sinc Interpolation for Continuous PRF Sampled Sequences Reconstruction in Spotlight SAR - CHEN Shiyang; HUANG Lijia; YU Lei (Leida xuebao, 2019)
This paper focuses on an improved imaging-algorithm for the spotlight Synthetic Aperture Radar (spotlight SAR) with continuous Pulse Repetition Frequency (PRF) variation in extremely high-resolution imaging-process. PRI variation is conventionally employed to resolve the problem of fixed blind ranges as well as the conflict of high-resolution and wide-swath; however, there are problems such as spectrum aliasing and ambiguous targets caused by nonuniform sampling. In this study, a novel sinc interpolation method is proposed to reconstruct a uniformly sampled signal from non-uniform Fourier Transform samples. Then a two-step processing approach combined with the novel sinc interpolation method is presented in the process of nonuniformly sampled echo imaging. The simulation proves the validity and accuracy of the proposed imaging algorithm. In addition, the computational cost of the novel sinc interpolation is further reduced compared to that of non-uniform Fourier transformation.